Ageing and popular culture - Blaikie, Andrew (Cambridge University Press, 1999)
Social theorists have yet to assess the cultural implications of population aging. This book traces the historical emergence of stereotypes of retirement and documents their latter-day dissolution, making striking use of visual sources, especially photography. Policy perceptions, media images and popular understandings are shown to suggest that the extended leisure phase known as the Third Age is breaking down old barriers between mid and later life. However, as the "gray market" perpetuates the quest for eternal youth, the biological realities of deep old age present an increasingly difficult challenge